2009
DOI: 10.1258/ijsa.2008.008271
|View full text |Cite
|
Sign up to set email alerts
|

Autopsies in HIV: still identifying missed diagnoses

Abstract: This study reviews the deaths and autopsies carried out over 23 years, 1983-2005, in a British Infection Unit in HIV patients. Of 115 HIV patients known to have died, we obtained data on 93%. Of this 80% were male, median age 38 (25-68) years; 83% were Caucasian; 12% Black African. Major risk factors were men who have sex with men, 52%; heterosexual in Africa, 17%; and injecting drug use, 8%. The commonest diagnosis pre- and post-autopsy diagnosis was pneumonia. Changes in diagnoses in the 38% who underwent au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…One of the important utilities of autopsy is the correlation between antemortem and postmortem diagnosis. A recent review from the UK spanning 23 years showed that the autopsy findings altered the primary diagnosis in 70% of cases, and that 36% of opportunistic infections were not diagnosed prior to death (Beadsworth et al, 2009). An Indian series showed discordance between antemortem and postmortem diagnosis in 42% cases (Lanjewar, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the important utilities of autopsy is the correlation between antemortem and postmortem diagnosis. A recent review from the UK spanning 23 years showed that the autopsy findings altered the primary diagnosis in 70% of cases, and that 36% of opportunistic infections were not diagnosed prior to death (Beadsworth et al, 2009). An Indian series showed discordance between antemortem and postmortem diagnosis in 42% cases (Lanjewar, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Both false positive as well as false negative antemortem diagnoses are described (Martinson et al, 2007). Infections such tuberculosis, Cytomegalovirus and invasive mycoses are missed with the highest rate (Antinori et al, 2009;Beadsworth et al, 2009;Eza et al, 2006;Tang et al, 2006;Wilkes et al, 1988).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the global trend of reducing the number of necropsies due to an increased use of radiological and laboratory tests in pre-mortem diagnosis, necropsy remains important even today, as the discrepancy rates between pre-mortem and postmortem findings in AIDS vary from 42 to 74%. Despite significant advances in diagnostic procedures, false-positive and false-negative diagnosis in the absence of necropsy still exist 8 , 9 , 10 , 11 , 12 . Necropsies are essential procedures for the quality control in university hospitals, and have helped to further understanding of the most frequent diseases in patients with HIV/AIDS 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages fail to organize immune response and, instead of arranging a granuloma, they pro liferate chaotically and place themselves in sheets which may totally obscure normal tissue structures. Langhans giant cells are absent or rare [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge not many autopsy-based studies on morbidity and mortality of HIV/AIDS population including large numbers of patients have been performed in Europe, including Baltic the countries [3,7,22,36].…”
Section: Introductionmentioning
confidence: 99%